Reinterpreting Jeremiah 29 amid the Deconstruction of Urban Space: A Theology of Exile in Response to Contemporary Gentrification - Sukanto Limbong; Daniel Panjaitan (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The massive urbanization and spatial restructuring of Indonesian metropolitan areas have intensified gentrification, systematically displacing lower-income communities from city centers to peripheries—a condition this study conceptualizes as